The Problem of Death - Zaksas, Irmija (Problemos, 1968)
I. Death is an objective biological process manifesting itself in the irreversible ceasing of the vital activity that is characteristic of any biological system. II. Death has its subjective aspect too: feelings, emotional experiences which are associated with this objective biological process and characteristic of a man. III. Subjective emotional experiences associated with death are comprehensively reflected in art. IV. Religion, in particular Christianity, pays great attention to the problem of death. The dogma about immortality of human soul plays an ever important part in strengthening the influence of the church. V. The history of philosophy deals with the problem of death in accordance with three principal aspects: 1) the grounding and criticism of the immortality of human soul; 2) the new sense of a man’s immortality as preservation of his works and good deeds; 3) emotional experiences associated with death as an essential element of man’s spiritual life – this aspect is being worked out by philosophy of existentialism in particular. VI. The present day -Marxist philosophers should work out the problem of death according to the three principal aspects taking into account the grounding of the scientific conception of ’s immortality and subjecting to severe criticism the interpretation of death practised by existentialism.